Synthesis of N-substituted amidinoheteroles and their reactivity towards Burgess reagent. (2nd January 2020) - Uchiyama, Yosuke; Kimura, Shinobu; Kurotaki, Takanori; Sawamura, Yukihiro; Kikuchi, Yuichi; Abe, Shinya; Runyon, Jason W.; Dolphin, Joshua S.; Schinnen, Christoph; Arduengo III, Anthony J.
Abstract: N -Substituted amidinoimidazoles and amidinopyrroles were synthesized by the reaction of 2-cyanoimidazole and 2-cyanopyrrole with the corresponding ammonium salts in the presence of AlMe3 in toluene under reflux conditions. With the aim to investigate the transformation of the N -substituted amidino group to isonitrilium ion, N -mesitylamidinoimidazole and N -diisopropylphenylamidinopyrrole were allowed to react with the Burgess reagent. Instead of the desired deamination product, 1, 2, 4, 6-thiatriazinone 1, 1-dioxides were produced, which are heterocycles containing a part of the Burgess reagent and the K -area of amidinoheteroles. Graphical Abstract: